Natural convection heat transfer from vertically arranged horizontal cylinders - Kalay, Sabri (My University, 2016)
Natural convection heat transfer in vertically arranged isothermal horizontal cylinders with unequal cylinder spacing in laminar flow has been investigated numerically in this thesis. The study consists of several investigations including variant numbers of cylinders as well as variant separation ratios. Investigations were carried out with 2, 3, 4, 5, 7 and 10 center-to-center vertically arranged 4.8 mm diameter copper cylinders. Considering the bottom cylinder as the first cylinder, the distance between the first and the second cylinder (S1) ranged as 2D, 3D, 5D, 7D and 10D, D being the outer diameter of the cylinder. The study was carried out in 5 different low Rayleigh numbers ranging from 93 to 280. The temperature of the cylinder surfaces was set as 303 K, 313 K, and 323 K whilst the ambient and the surrounding wall's temperature was 293 K and 303 K. The results show that increasing spacings between cylinders within a bundle enhance the heat transfer in the upper cylinders and the bundle.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Keywords: Natural convection; Horizontal cylinders; Increasing spacings